Conversations, controversy, and calculations in an unpublished chilam balam of Yucatan - Molly Tun (Universidade Estadual de Campinas, 2017)
In this article I explore the benefits and dangers of intercultural contact in the context of the creation and diffusion of Chilam Balam books, sacred texts compiled mainly during the colonial period and used by Maya communities of Yucatan.  I present the results of my fieldwork to the area which include the narrative of the disappearance and re-creation of an unpublished Chilam Balam as well as a partial reproduction of its contents including a chapter on Maya Numbers and a collection of Maya hieroglyphs.  This reproduction of an original unpublished Chilam Balam manuscript is a unique contribution to the field of Maya studies and evidence of the Maya episteme regarding numbers, time, and the universe.